The effect of acupuncture on quality of life in patients with irritable bowel syndrome: A systematic review and meta-analysis - Jun Zhou; Narendra Lamichhane; Zhifang Xu; Jiaqi Wang; Vo Dai Quynh; Jing Huang; Feifei Gao; Meidan Zhao; Zelin Chen; Tianyi Zhao (PLoS ONE, 2025)
Background Acupuncture has been used to improve the quality of life (QoL) of patients in clinical settings. However, the effect of acupuncture on QoL in patients with irritable bowel syndrome (IBS) remains unclear. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of acupuncture on the QoL of patients with IBS. Method PubMed, Cochrane Central Register of Controlled Trials, Embase, and Web of Science were screened from inception to September 2023. RCTs published in English comparing acupuncture with sham acupuncture, usual care, pharmacological interventions, or other therapies were analyzed for QoL in patients with IBS. The primary outcome was QoL and secondary outcomes were the IBS-symptom severity scale (IBS-SSS) and abdominal pain. The Cochrane Collaboration recommendations were used to assess the risk of bias. Findings Fourteen articles with 2,038 participants were included. The pooled result showed acupuncture can significantly improve the QoL of patients with IBS compared to the conventional treatment (MD = 6.62, 95% CI, 2.30 to 10.94, P<0.001, I2 = 72.45%). Additionally, acupuncture was superior to other interventions in relieving the symptoms’ severity of IBS (MD = -46.58, 95% CI, -91.49 to -1.68, P<0.001, I2 = 90.76%). Nevertheless, acupuncture was not associated with abdominal pain reduction (MD = -0.35, 95% CI, -0.91 to 0.20, P = 0.21, I2 = 0.00%). Lower adverse events were observed in the acupuncture group. Thus, the quality of this study was relatively high. Conclusion The meta-analysis showed that acupuncture improves QoL and symptom severity in patients with IBS and that the optimal parameters for acupuncture to improve QoL in patients with IBS are 30 minutes of acupuncture per session, less than or equal to five sessions per week, and a 4-week course of treatment. However, more high-quality clinical trials are needed to provide stronger evidence.